2017
DOI: 10.3389/fcimb.2017.00081
|View full text |Cite
|
Sign up to set email alerts
|

P. acnes-Driven Disease Pathology: Current Knowledge and Future Directions

Abstract: This review discusses the biology and behavior of Propionibacterium acnes (P. acnes), a dominant bacterium species of the skin biogeography thought to be associated with transmission, recurrence and severity of disease. More specifically, we discuss the ability of P. acnes to invade and persist in epithelial cells and circulating macrophages to subsequently induce bouts of sarcoidosis, low-grade inflammation and metastatic cell growth in the prostate gland. Finally, we discuss the possibility of P. acnes infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…The Gram‐positive, anaerobic, slow‐growing bacterium Cutibacterium acnes (formerly Propionibacterium acnes ) is responsible for recrudescent or chronic acne, and can also affect implants, such as cardiovascular devices and prosthetic joints (Achermann, Goldstein, Coenye, & Shirtliff, 2014; Lee, Byun, & Kim, 2019). More than 50% of C. acnes isolates are resistant to topical macrolides, making treatment challenging (Leheste et al, 2017; Portillo, Corvec, Borens, & Trampuz, 2013; Van Boeckel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Gram‐positive, anaerobic, slow‐growing bacterium Cutibacterium acnes (formerly Propionibacterium acnes ) is responsible for recrudescent or chronic acne, and can also affect implants, such as cardiovascular devices and prosthetic joints (Achermann, Goldstein, Coenye, & Shirtliff, 2014; Lee, Byun, & Kim, 2019). More than 50% of C. acnes isolates are resistant to topical macrolides, making treatment challenging (Leheste et al, 2017; Portillo, Corvec, Borens, & Trampuz, 2013; Van Boeckel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…P. acnes is a part of commensal microbiota and is generally present in human skin, hair follicles, and mucous membranes [5,18]. It is well known for its involvement in the pathogenesis of acne vulgaris [19]; moreover, its role in various postoperative infections such as endocarditis, endophthalmitis, and central nervous system (CNS) infections has been reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…acnes is a part of commensal microbiota and is generally present in human skin, hair follicles, and mucous membranes [5,18]. It is well known for its involvement in the pathogenesis of acne vulgaris [19]; moreover, its role in various postoperative infections such as endocarditis, endophthalmitis, and central nervous system (CNS) infections has been reported [5]. In addition, P. acnes can invade and persist in epithelial cells and circulating macrophages in its intracellular latent form [5], which results in chronic inflammation such as sarcoidosis [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Propionibacterium acnes ( P . acnes ), a skin bacterium closely associated with acne, is reported to be associated with prostatic inflammation and carcinogenesis [ 7 9 ]. Several observational studies have found a possible link between a history of acne and prostate cancer risk but with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%